Utopies et robinsonnades contemporaines - Jean-Paul Engélibert (Carnets)
The island genres of robinsonnade and utopia, which we might think obsolete in the 21st century, still play an important role in contemporary French literature and cinema. Xabi Molia's novel Les Jours sauvages, Alain Damasio's Les Furtifs and Arthur Harari's film Onoda, 10,000 Nuits dans la Jungle renew these genres by playing on the stereotypes of island adventures and turning them towards contemporary issues: Damasio's utopian island evokes a "zone to defend" inspired by the social and ecological struggles of the 2010s in France, Molia's collective robinsonade questions the transmission of a violent history and Harari's makes the island the place of absolute fidelity to a promise, displacing without forgetting the stakes of Daniel Defoe's Robinson Crusoe. In this way, the island still provides us today with narrative resources for thinking about the present.